2017
DOI: 10.18632/oncotarget.15710
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hematological diseases following haploidentical donor hematopoietic stem cell transplant compared with matched sibling and unrelated donor

Abstract: Autoimmune hematological diseases (AHDs) occur more frequently than other autoimmune complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and are often refractory to treatment. This study was to analyze the incidence and risk factors of AHDs as well as their response to treatment. Four hundred and forty-five adult malignant hematopoietic disorders underwent allo-HSCT were enrolled in this retrospective study, including 124 haploidentical donor (HRD), 140 unrelated donor (MUD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…High‐resolution molecular techniques were used to detect HLA typing of recipients and donors . All patients received myeloablative conditioning regimens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High‐resolution molecular techniques were used to detect HLA typing of recipients and donors . All patients received myeloablative conditioning regimens.…”
Section: Methodsmentioning
confidence: 99%
“…Responses were mainly evaluated at 4 and 12 weeks after initial treatment. Thresholds for determining response were based on standard and previous studied outcome criteria for AIHA and Evans syndrome . The criteria for effectiveness were as follows: (a) CR: Hb level of 12 g/dL and a platelet (PLT) level of 100 g/L or more in the absence of a transfusion without features of hemolysis (normal bilirubin and lactate dehydrogenase levels ± normal haptoglobin level if performed); (b) partial response (PR): Hb level of at least 10 g/dL with an increase of at least 2 g from baseline and a PLT level of at least 50 g/L; (c) NR: failure to meet the above two criteria; and (d) the overall response (OR) rate included both CR and PR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study showed no imbalance between T‐ and B‐cell reconstitution at 90 and 180 days following HSCT in patients who developed AIC. In this study, T‐ and B‐cell profiles at the time of AIC formation were not known . Therefore, the role of Treg and T/B‐cell imbalance in post‐ HSCT AIC warrants further study.…”
Section: Discussionmentioning
confidence: 87%
“…One article was excluded because it did not mention immune cytopenia complications. This resulted in 22 primary evaluable articles …”
Section: Resultsmentioning
confidence: 99%